Biophysical Simulations Support Schooling Behavior of Fish Larvae Throughout Ontogeny - Berenshtein, Igal; Paris, Claire B.; Gildor, Hezi; Fredj, Erick; Amitai, Yael; Kiflawi, Moshe (Frontiers in Marine Science, 2018)
Schooling is very common in adult and juvenile fish, but has been rarely studied during the larval stage. Recent otolith micro-chemistry studies of coral reef fish have demonstrated that cohorts of larvae can move through similar paths and settle within a few meters one from another. However, little is known about the processes involved in the formation and maintenance of these cohorts. Here we use a biophysical modeling approach to examine whether local hydrodynamics, various individual behaviors, or larval schooling can explain cohesive patterns observed for Neopomacentrus miryae in the Gulf of Aqaba/Eilat (Red Sea), and whether schooling is feasible in terms of initial encounter probability and cohesiveness maintenance. We then examine the consequences of schooling behavior on larval settlement success and connectivity. Our results indicate that: (1) Schooling behavior is necessary for generating cohesive dispersal patterns, (2) Initial larval encounter of newly-hatched larvae is plausible, depending mainly on initial larval densities, and patchiness, And (3) schooling behavior increases the rate of larval settlement while decreasing the percentage of realized connections. Together with mounting evidence of cohesive dispersal, this numerical study demonstrates that larval schooling throughout the pelagic phase is realistic, and has a significant effect on settlement success and connectivity patterns. Future research is needed to understand the mechanisms of fission-fusion dynamics of larval cohorts and their effect on dispersal. Our findings should be considered in future efforts of larval dispersal models, specifically in the context of marine connectivity and the planning of marine protected area networks.